Does 5 + 5 Equal Better Radiation Treatment Plans in Head and Neck Cancers? - Mark T. Corkum, MD, MSc; Sylvia Mitchell, MRT(T); Varagur Venkatesan, MBBS; Nancy Read, MD; Andrew Warner, MSc; David A. Palma, MD, PhD (Advances in Radiation Oncology, 2019)
Purpose: Accurate contouring in head and neck cancer (HNC) is critical. International consensus guidelines recommend the 5 + 5 mm rule for expansions around the primary tumor, wherein high- and low-dose clinical target volumes (CTV-P1 and CTV-P2, respectively) are created using successive 5 mm expansions on the gross tumor volume. To our knowledge, the necessity of a low-dose CTV-P2 has never been assessed; therefore, we evaluated the dosimetric impact of adding a CTV-P2 expansion using the 5 + 5 mm rule compared with contouring with a high-dose CTV-P1 alone. Methods and materials: A retrospective study of clinically delivered (chemo)radiation therapy treatment plans for HNC was conducted. All patients were treated with 70 Gy in 35 fractions using volumetric modulated arc therapy in a single phase. CTV-P2 was retrospectively contoured per guidelines as a 5 mm expansion on CTV-P1 from the clinical plan, carving off specified barriers to spread. We used a 5 mm planning target volume (PTV) expansion. Our primary outcome was whether 95% of the volume of the PTV for the CTV-P2 contour (ie, PTV-P2) received at least 56 Gy. To assess dose falloff, the coverage of a PTV ring structure was created by subtracting PTV-P1 from PTV-P2. Results: Twenty-seven patients from 4 HNC subsites (base of tongue, tonsil, hypopharynx, and supraglottic larynx) were included. In all 108 treatment plans, at least 95% of the PTV-P2 structure received at least 56 Gy. The minimum volume of the PTV-P2 structure receiving at least 56 Gy was 97.4%. Eight of 108 treatment plans had borderline coverage of the PTV ring substructure alone. Conclusions: Adding a CTV-P2 structure using the 5 + 5 mm rule had no dosimetric impact, adds contouring time, adds treatment planning complexity, and could potentially introduce errors. The 5 + 5 mm rule may have value in other settings, such as when smaller PTV margins are used, and warrants further evaluation with prospective or randomized studies.